Analysis of training methods used in the development of Chinese martial arts athletes - Yang, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Based on the abundant collection of related documents focusing on Martial Arts techniques, this paper aims to advance a scientific concept for Martial Arts training. Methods Literature review and comparative and logical analyses methods were used to explore the basic training of Martial Arts athletes and the major factors influencing the development of this training. Results The basic training methods used in Martial Arts includes technique, skills and basic movement training. Technique training teaches the different styles and common standards required for the various sections of Martial Arts. Athletes should start with general basic training for the first one to three years of Martial Arts training, followed by more specialized training. When the athlete has trained for more than 10 years, the aim is to maintain the athlete`s skills and competitive level. Review of the factors influencing the development of training suggested that more attention should be paid to the current trend whereby athletes and coaches are focusing increasingly on the technical and advanced training without focussing on the fundamentals, which has already resulted in a lower quality of performance in the Taolu of Martial Arts. Factors influencing this decrease in quality include (1) a lack of mental attention; (2) the development of competition rules; and (3) the effect of adopting deferent values. Discussion / Conclusions Martial Arts is a traditional Chinese sport and represents a combination of sports and culture. Martial Arts require more protection, systematization, support and understanding to assist their development and promotion of traditional sports. The lack of basic training represents a major problem in the course of development of the Martial Arts and has a bearing on the development of young athletes and the future of this sport.